How Does the Degree of Export Dependence Affect China’s Clean Drinking Water? - Yahia, Abdelrahim A M; Ahmed, Ismaeel A M; ALhassan, Nada R A (Asian Journal of Economic Modelling, 2021)
Access to clean drinking water has become an increasingly urgent concern for China's government in the current decade. However, with the continuous economic growth, high export orientation, and investment in infrastructure, the interconnected challenges related to clean drinking water are stressed. This study aims to explore the effects of exports, in addition to such greatest factors affecting clean drinking water in China during 2000–2017. To provide comprehensive results we employ a co-integration approach, and conduct the empirical analysis by applying a semi-parametric regression model. Empirical results show that while the degree of export dependence exerted on clean drinking water negative effects, but has no predictive linear Granger cause. The results from the nonlinear model indicate that the effect of exports on clean drinking water shows an inverted “U-shaped” nonlinear impact in the national and urban levels. This indicates that only in the earlier stages, the degree of export dependence driving clean drinking water, and did not play a promoting role in the later stages. On the contrary, it exerts a positive “U-shaped” pattern at the rural level. The evidence for the impact of income inequality on expanding or contracting access to clean drinking water at overall levels is mixed.